Healing process of dog teeth after post space preparation and exposition of the filling material to the oral environment - Barbosa Henrian Gonzaga; Holland Roberto; Souza Valdir de; Dezan Júnior Eloi; Bernabé Pedro Felício Estrada; Otoboni Filho José Arlindo; Nery Mauro Juvenal (Fundação Odontológica de Ribeirão Preto, 2003)
The purpose of this study was to observe the influence of coronal leakage on the behavior of periapical tissues after root canal filling and post space preparation. Forty root canals of dogs' teeth were instrumented and filled by the lateral condensation technique with gutta percha points and the cements Sealer 26 and Roth. After post space preparation, the remaining filling material was either protected or not protected with a plug of the temporary cement Lumicon. After root canal exposition to the oral environment for 90 days, the animals were killed and specimens were removed and prepared for histomorphological analysis. The Brown and Brenn technique showed 70% of cases with microorganism leakage for Roth cement, and 20% with Sealer 26. When a plug of Lumicon was employed, there was 30% leakage for Roth cement and 0% for Sealer 26. A chronic inflammatory reaction was more frequently observed with Roth cement than with Sealer 26. It was concluded that a plug of Lumicon was efficient in controlling microorganism coronal leakage (p=0.05), and that Sealer 26 was more biocompatible and sealed root canals better than Roth sealer (p=0.01).